Topics on Riemann surfaces and Fuchsian groups - Bujalance García, Emilio 1953-; Costa, Alvaro Filipe da; Martínez, E. 1952- (London Mathematical Society lecture note series, 2001)
Presents a cross-section of different aspects of Riemann surfaces, introducing the reader to the basics as well as highlighting new developments in the field. It provides a mixture of classical material, recent results and some non-mainstream topics. The book is based on lectures from the conference Topics on Riemann Surfaces and Fuchsian Groups held in Madrid to mark the 25th anniversary of the Universidad Nacional de Educación a Distancia. For those wishing to pursue research in this area, this volume offers a valuable summary of contemporary thought and a source of fresh geometric and algebraic insights. The book will be suitable for graduate courses, as well as providing a useful reference for those already working in geometry, group theory, complex analysis, algebraic geometry, topology and theoretical physics